A Connection of Optimum Logistic and Energy Consumption in Hiking - Sugeng Waluyo; Dewi Tria Setyaningrum; Indro Prakoso; Tigar Putri Adhiana; Rani Aulia Imran (Journal of Applied Sciences, Management and Engineering Technology, 2022)
In this work, we aim to provide a connection between energy consumption during hiking and its relation to optimum logistic preparations in mountaineering-based tourism. Such energy consumption is calculated based on data from hiking track profiles and heart rate of persons taking the track. It is then used as input to solve optimization problems in term of the logistic preparations. Here, we demonstrate such connection based on the actual condition of hiking track in the Mount of Sindoro, Central Java, Indonesia.